L'État de droit démocratique - Jouanjan, Olivier (Array, 2019)
In Europe, democracy has a bright future. Not one democratic mechanism, however direct, cannot guarantee direct democracy. Therefore, the theory of populism by theoretician Carl Schmitt is analyzed « thoughts on Schmitt against Schmitt : Ernst-Wolfgang Böckenförde“. Furthermore, the democratic myth is discussed and its ideology. The state of rule of law of modern democracy and the two faces of modern democracy are analyzed. The need to participate in civil society in administrative control is stressed. The relation of the tension between democracy and rule of law is observed. The need to consider the concept of considering modern democracy in relation to the idea of rule of law, democracies under conditions of modern politics on the basis of which Böckenförde, referring to Hegel, calls the problem „division “are emphasized. It is precisely from this problem that Böckenförde shows that modern democracy can only be representative. Representation is a fundamental principle of the rule of law while representation means a system of formation necessary for expressing the political will of the people. Every formation of the collective process means the introduction of standards of procedure, significant guarantees and formal conditions of this process.